A study on the impact of smoking and alcoholism as determinant factors in the prognosis and outcome of diabetic foot ulcer disease - Pal, Bikramjit; Raveender, Nagaraju; Sudipta, Pal (International Journal of Research in Medical Sciences, 2016)
Background: This is an observational study to determine the relation between the life style factors like smoking and chronic alcoholism with the severity of the diabetic foot ulcer disease; its implications and prognosis and outcome with particular reference to the incidence of amputation and the duration of the hospital stay. This study was done in 89 patients who were admitted in the surgical wards of two large private medical colleges in India: KPC Medical College and Hospital, Kolkata, West Bengal and Bhaskar Medical College and Hospital, Yenkepally Village, Ranga Reddy District, Telengana. In our study, we explored the relationship between two determinant factors - smoking and chronic alcoholism with the increased incidence of amputation and prolonged hospital stay in a diabetic cohort. It has been found from this study that the severity of diabetic foot ulcer disease is more in patients who were addicted to either smoking, alcohol or both. Methods: The study was done on 89 patients who were admitted in the surgical wards of the following teaching hospitals in India - KPC Medical College and Hospital which deals mostly with middle income group of urban population (Rs.7594 to 15188) and Bhaskar Medical College and Hospital which deals mostly with low income group of semi-urban population (Rs.4556 to 11361) as per Kuppuswamy’s socio-economic status scale (updating for 2012). The youngest patient was from semi-urban area aged 26 years and the oldest patient was from urban area aged 83 years. The outcome and prognosis of the diabetic foot ulcer disease were assessed with the incidence of amputation and duration of hospital stay in relation to the two determinant factors of smoking and alcoholism. Results: The diabetic patients who were smokers and/or chronic alcoholic underwent more amputations with concomitant longer hospital stay than the patients who had no addiction to these substances. The prognosis was worse in the subgroup of patients who were both smoker and chronic alcoholic. Conclusions: The study observed that the prognosis and outcome of a diabetic foot ulcer disease changes significantly in patients who are addicted to smoking and alcoholism with higher incidence of amputation and longer hospital stay.